The Transformation of Kizukai Habitus on Asian Trainee in Japan: Striving and Competition of Labor Market in ASEAN - Prabowo, Roberto Masami; Mahzuni, Dade; Risagarniwa, Yuyu Yohana; Rustam, Muhammad Reza (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2024)
In the 1990s, Japan faced a severe economic downturn known as the